O clima urbano de Mossoró (RN) : o subsistema termodinâmico - Saraiva, Ana Luiza Bezerra da Costa (2014)
Due to population growth and the growth of economic activities, the city area of the municipality of Mossoró, in the State of Rio Grande do Norte, has experienced an inordinate expansion of urban area that started from 1980s. Currently the urban area is 11.58 km² which reside 259.815 inhabitants (IBGE , 2010) which means 90% of the city population. Given this context, this work aims to meet the current dynamics of the thermal field in the municipality of Mossoró, a city located in the semiarid region of northeastern Brazil, through the analysis of concurrent data from weather elements, such as: temperature and relative humidity. Based on different environmental and social contexts of the municipality, nine points were selected, seven in urban area and two in rural area as reference sites for carrying out the analysis of the different behaviors of climatic elements. Sampling sites in the urban area and rural area sought to represent different land uses and occupations that municipality. The survey was conducted over seven days in April (rainy season) , 7 days in July (period where the lowest temperatures are found) and 7 days in October (warmer and drier period) totaling just a collection of data over 21 days not consecutive, during the year 2012. For the fieldwork methodology developed by Mendonça (2003), based on the Urban Climate System of Monteiro (1976) for the study of urban climate of cities of medium and small size was used. Collections were made at fixed sampling points for 24 hours over 21 days. Heat islands and more intense droughts islands found in Mossley were identified during morning and afternoon, reaching critical values of temperature and humidity at 14h. Through spatial data has been established that the central and areas for urban expansion in the western portion, areas showed the most intense heat islands and dry islands.